Juridical Study of Exhibitionism According to Criminal Law and Health Law - Gunawan, Arul; Yustrisia, Lola; Munandar, Syaiful (JURNAL MAHASISWA YUSTISI, 2024)
Exhibitionism refers to the act of displaying one's body parts or vital organs to others with the intention of attaining sexual gratification. This is done to achieve sexual gratification through the act of masturbation while engaging in imaginative thoughts. Exhibitionism is classified as a paraphilia, which falls under the category of sexual preference disorders. This study examines the legal and health aspects of exhibitionism. The research methodology employed in this study is normative research. Data sources were obtained through a comprehensive review of relevant literature, and were analyzed using analytical descriptive analysis. The findings of this study indicate that exhibitionism is influenced by various factors, including both internal and external factors, as well as perspectives from health law. The regulations pertaining to moral offenses are established in Article 406, paragraph 1 and paragraph 2 of the Criminal Code, as well as Article 414 of the Criminal Code, and Law Number 44 of 2008, which addresses the issue of pornography. Acts of exhibitionism encompass behaviors that transgress societal standards of decency. Individuals who engage in exhibitionism can face legal charges under Article 406 of the Criminal Code, as well as Article 10 and Article 36 of Law no. 44 of 2008, which specifically addresses pornography